Does hepatitis C increase the accumulation of advanced glycation end products in haemodialysis patients? - Arsov, Stefan; Graaff, Reindert; Morariu, Aurora M; van Oeveren, Wim; Smit, Andries J; Bushletikj, Irena; Trajcheska, Lada; Selim, Gjulshen; Dzekova Vidimliski, Pavlina; Stegmayr, Bernd; Shikole, Aleksandar; Rakhorst, Gerhard (Oxford University Press (OUP), 2010)
Hepatitis C may cause increased levels of oxidative stress that contribute to accumulation of advanced glycation end products (AGEs), which increase the risk of cardiovascular disease (CVD). The aim of this study was to determine the influence of hepatitis C on AGE accumulation in haemodialysis patients.